Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding